Bridging the gap: examining healthcare providers’ beliefs and recommendations in cardiac rehabilitation and the determinants of their practices in China - Jiabin Zang; Zhehao Zhang; Zhan Gao; Songhuan Jiang; Yan Weng; Xuechen Hu (BMC Health Services Research)
Abstract Background Cardiac rehabilitation (CR) can improve the prognosis of cardiovascular diseases. Healthcare providers’ recommendations play a key role in promoting patient participation in CR. This study aimed to assess healthcare professionals’ beliefs of CR in China, explore the current status of CR recommendations to patients, and identify the factors influencing their recommendation behavior. Methods A cross-sectional survey was conducted among cardiovascular doctors, nurses, rehabilitation therapists and general practitioner from healthcare institutions across the country. A total of 1,120 valid questionnaires were collected. The survey included demographic information, the Chinese version of the Recommending Cardiac Rehabilitation (ReCaRe) scale to assess beliefs regarding CR, CR resources, knowledge of CR, and CR recommendation behavior. Binary logistic regression was performed to identify the factors influencing CR recommendation behavior. Results The total score of the ReCaRe scale was 60.80 ± 7.36, with the perceived severity and susceptibility scoring 3.98 ± 0.60, perceived service accessibility at 2.72 ± 0.96, and the perceived benefits and barriers 4.13 ± 0.56. It was reported by 56.5% of healthcare providers that they had recommended CR to patients. However, only 34.6% of participants were familiar with the specific details of CR. It was expressed by 86.0% of healthcare providers that there is a need for more CR resources and training. The predictive factors for healthcare professionals’ CR recommendation behavior included familiarity with CR content and the five CR prescriptions, professional title, availability of CR services, hospital type, position, department and age. Conclusions There is an urgent need to provide healthcare professionals with more resources and training to deepen their understanding of CR, while also addressing the utilization and accessibility of CR services, in order to enhance their CR recommendation behavior.